2019
DOI: 10.3349/ymj.2019.60.7.611
|View full text |Cite
|
Sign up to set email alerts
|

Family with Sequence Similarity 83 Member H Promotes the Viability and Metastasis of Cervical Cancer Cells and Indicates a Poor Prognosis

Abstract: Purpose Family with sequence similarity 83 member H (FAM83H) plays key roles in tumorigenesis. However, the specific roles of FAM83H in cervical cancer (CC) have not been well studied. Materials and Methods The RNA-seq data of 306 CC tissues and three normal samples downloaded from The Cancer Genome Atlas were used to analyze the expression of FAM83H. The Kaplan-Meier method was used to draw survival curves. Associations between FAM83H expression and clinicopathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
4
13
0
Order By: Relevance
“…Accordingly, higher mRNA expression of FAM83H was also considerably related with shorter OS and PPS of lung cancer patients. Consistent with our results, Chen et al (2019) demonstrated that FAM83H is increased in cervical cancer tissues and that high FAM83H expression tends to worsen the OS. In addition, suppression of FAM83H refrained proliferation, colony formation, migration, and invasion of CC cells through inactivating PI3K/AKT pathway ( Chen et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Accordingly, higher mRNA expression of FAM83H was also considerably related with shorter OS and PPS of lung cancer patients. Consistent with our results, Chen et al (2019) demonstrated that FAM83H is increased in cervical cancer tissues and that high FAM83H expression tends to worsen the OS. In addition, suppression of FAM83H refrained proliferation, colony formation, migration, and invasion of CC cells through inactivating PI3K/AKT pathway ( Chen et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our results, Chen et al (2019) demonstrated that FAM83H is increased in cervical cancer tissues and that high FAM83H expression tends to worsen the OS. In addition, suppression of FAM83H refrained proliferation, colony formation, migration, and invasion of CC cells through inactivating PI3K/AKT pathway ( Chen et al, 2019 ). Further analysis demonstrated that the patients were categorized by cutoffs of 804 for FAM83H low expression and high expression and achieved a 0.9454545/0.8974359 specificity/sensitivity in distinguishing poor survival from OS.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, FAM83H was found to be up‐regulated and positively correlated with FAM83H‐AS1 expression in ESCC tissues. Moreover, FAM83H functioned as tumour promoter by facilitating oesophageal cancer cells viability and invasion, which was consistent with previous studies in cervical cancer and osteosarcomas 21,22 . Further experiments indicated that FAM83H‐AS1 regulated the expression of FAM83H at transcriptional and post‐transcriptional levels in oesophageal cancer cells.…”
Section: Discussionsupporting
confidence: 90%
“…Especially, the combined expression patterns of FAM83H-N and SCRIB-N were strongly predictive of the survival of gastric carcinoma patients. Consistently, FAM83H was an indicator of poor prognosis of cancers of the liver [4], kidney [5], uterus [10,12], and bone [8]. The expression of SCRIB mRNA was also higher in hepatocellular carcinomas compared with non-tumorous liver tissue [20].…”
Section: Discussionmentioning
confidence: 72%
“…Higher expression of FAM83H increases the proliferation and invasiveness of cancer cells [4,[8][9][10]. The expression of FAM83H is higher in human cancer tissue compared with normal tissue [10][11][12] and higher expression of FAM83H is associated with poor prognosis of cancers of the uterus [10,12], liver [4], kidney [5], and bone [8]. However, FAM83H is a favorable prognostic factor of glioma and head and neck cancers [12].…”
Section: Introductionmentioning
confidence: 99%